Zbrodnia w afekcie. Afektywny potencjał figury wampira-seryjnego mordercy w prozie Tadeusza Konwickiego - Piskorska, Jadwiga (Zagadnienia Rodzajów Literackich, 2025)
The article analyzes the figure of the vampire-lust-murderer in the works of Tadeusz Konwicki, focusing on the novels Nic albo nic (1971) and Rzeka podziemna, podziemne ptaki (1984). The figure is set in the social and cultural context of communist Poland, in which the vampire — identified as a serial killer — becomes a vehicle for repression and fears. The author draws on the theories of gothic criminology to show how the socially constructed image of the “red vampire” influences the reception of the analyzed novels. The text primarily emphasizes the affective dimension of Konwicki’s prose, in which the vampire functions not as a figure of horror, but as a tool of subversion. The grotesqueness, the fragmentary nature of the narrative, the specific poetics of confession and, above all, the sometimes-masochistic attitude of the vampire of the interpreted novels intensify the effect of affective disorientation, which undermines the binary divisions between torturer and victim, reality and fiction, individual and collective experience. The analysis indicates that the vampire in Konwicki’s literature has an ambiguous function: it combines elements of the masochistic literary subject, victim and aggressor, inducing subversion and new tactics of resistance.